Enterprise Risk Management Disclosure and Investment Efficiency: A Moderation Role Of CEO Power - Dewi Diah Fakhriyyah; Junaidi Junaidi; Nabila Maharani (Cita Konsultindo Research Center, 2023)
This study aims to provide empirical evidence regarding enterprise risk management disclosure’s effect on investment efficiency and also the moderation role of CEO power on enterprise risk management disclosure’s effect on investment efficiency. This is quantitative research. Investment efficiency is measured as deviations from expected investment using a model that predicts investment as a function of growth opportunities, while enterprise risk management disclosure is measured through the risk management disclosure index carried out by the company, and CEO power is measured by the CEO Power Index. The data source is annual report of a public company, and the sample is a company listing at Index LQ 45. The research results show that enterprise risk management disclosure has a positive effect on investment efficiency, but CEO power cannot moderate enterprise risk management disclosure’s effect on investment efficiency. Based on the result, CEO Power as a predictor variable has a positive effect on investment efficiency. This research contributes to the agency theory that reducing information asymmetry can increase investment efficiency by providing broader ERM disclosures and greater CEO power. Keywords: Enterprise Risk Management, Investment Efficiency, CEO Power, Agency Theory